1990
DOI: 10.1136/gut.31.3.329
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting colectomy rate in ulcerative colitis: an epidemiologic study.

Abstract: Factors affecting colectomy rate were studied in a retrospective population based series of 1586 patients with ulcerative colitis, in Stockholm County during 1955-84. Five hundred and sixty eight patients (36%) had total colitis at diagnosis, 603 patients (38%) left sided colitis, and 397 patients (25%) proctitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
78
3
18

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(110 citation statements)
references
References 13 publications
11
78
3
18
Order By: Relevance
“…Previous studies reported that a considerable number of patients with left-sided UC experienced disease progression (Leijonmarck et al, 1990;Farmer et al, 1993). In our series, 25 patients out of 137 (18%) with total colitis were first regarded as being of the less extensive type.…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies reported that a considerable number of patients with left-sided UC experienced disease progression (Leijonmarck et al, 1990;Farmer et al, 1993). In our series, 25 patients out of 137 (18%) with total colitis were first regarded as being of the less extensive type.…”
Section: Discussionmentioning
confidence: 68%
“…It is estimated that approximately 20 to 30% of patients with UC ultimately require a surgical resection. [1][2][3] Total proctocolectomy with ileal pouch-anal anastomosis (IPAA), which was first described in 1978 by Parks and Nicholls, 4 has become established as the standard surgical treatment for patients with UC. The problems with IPAA are that the excision close to the anal sphincter may result in impaired anal function that may cause neurologic damage to the rectum, in turn resulting in urinary and sexual dysfunction.…”
mentioning
confidence: 99%
“…In the studies from Western countries, surgical operations are reportedly performed in 20%-25% of patients with UC (1,30), and in a population-based study from Stockholm, the cumulative risk of colectomy after 5 years was 20% (95% CI, 18%-22%). Langholtz et al, also reported a cumulative risk of 20% after 5 years in Copenhagen (31,32). Total colectomy was performed in just 61 of our 612 patients (9.9%).…”
Section: Discussionmentioning
confidence: 52%